The Russian-Ukrainian political divide - Amelie F. Constant; Martin Kahanec; Klaus F. Zimmermann (Institute for the Study of Labor (IZA), 2006)
The Orange Revolution unveiled significant political and economic tensions between ethnic Russians and Ukrainians in Ukraine. Whether this divide was caused by purely ethnic differences or by ethnically segregated reform preferences is unknown. Analysis using unique micro data collected prior to the revolution finds that voting preferences for the forces of the forthcoming Orange Revolution were strongly driven by preferences for political and economic reforms, but were also independently significantly affected by ethnicity; namely language and nationality. Russian speakers, as opposed to Ukrainian speakers, were significantly less likely to vote for the Orange Revolution, and nationality had similar effects.
urn:nbn:de:101:1-20080429101
Keywords: 330